2023
DOI: 10.1161/jaha.123.031255
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) Testing Trends in a Large Academic Health System in the United States

Harpreet S. Bhatia,
Samantha Hurst,
Paresh Desai
et al.

Abstract: Background Despite its high prevalence and clinical significance, clinical measurement of lipoprotein(a) is rare but has not been systematically quantified. We assessed the prevalence of lipoprotein(a) testing overall, in those with various cardiovascular disease (CVD) conditions and in those undergoing cardiac testing across 6 academic medical centers associated with the University of California, in total and by year from 2012 to 2021. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…18 Despite the clinical significance of elevated Lp(a) and current guideline recommendations for once-in-a-lifetime universal screening for this condition, only 0.4% have undergone Lp(a) testing which aligns with the reported measures from other health systems and claims databases. [15][16][17] Adherence to guideline recommendations in realworld clinical practice remains a challenge in different domains of medicine and cardiology with implementation science being an active area of interest and research. 19,20 The feasibility of deploying ARISE within health systems suggests its potential as an effective strategy to bridge this gap and promote widespread Lp(a) testing and case identification, thereby enhancing care quality and patient outcomes on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Despite the clinical significance of elevated Lp(a) and current guideline recommendations for once-in-a-lifetime universal screening for this condition, only 0.4% have undergone Lp(a) testing which aligns with the reported measures from other health systems and claims databases. [15][16][17] Adherence to guideline recommendations in realworld clinical practice remains a challenge in different domains of medicine and cardiology with implementation science being an active area of interest and research. 19,20 The feasibility of deploying ARISE within health systems suggests its potential as an effective strategy to bridge this gap and promote widespread Lp(a) testing and case identification, thereby enhancing care quality and patient outcomes on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…This could stem from healthcare providers preferentially ordering Lp(a) tests for high-risk patients or those with recurrent cardiovascular events. [15][16][17] Moreover, the gradual dissemination of new medical practices and the potential future availability of targeted therapeutics may catalyze the broader adoption of universal Lp(a) screening. However, there is a wide gap between existing knowledge and its practical application, wherein ARISE implementation within health systems represents a promising avenue to address this disconnect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of more than 5 million adults at six academic medical centres affiliated with the University of California in the United States found that the frequency of Lp(a) determination remains very low at 0.3%, with a 4% prevalence among patients with cardiovascular diseases [ 11 ]. A study including all adults (4.6 million) registered with the largest health organisation in Israel showed that only 0.1% had their Lp(a) levels tested between 2015 and 2021 [ 12 ].…”
Section: How Often Is the Lp(a) Concentration Tested?mentioning
confidence: 99%